The Intestinal Epithelium: Central Coordinator of Mucosal Immunity - Allaire, Joannie M.; Crowley, Shauna M.; Law, Hong T.; Chang, Sun Young; Ko, Hyun Jeong; Vallance, Bruce A. (Trends in Immunology, 2018)
The gastrointestinal (GI) tract represents a unique challenge to the mammalian immune system. It must tolerate the presence of the luminal microbiota and thus not respond to their products, but still protect the intestinal mucosa from potentially harmful dietary antigens and invading pathogens. The intestinal epithelium, composed of a single layer of cells, is crucial for preserving gut homeostasis and acts both as a physical barrier and as a coordinating hub for immune defense and crosstalk between bacteria and immune cells. We highlight here recent findings regarding communication between microbes and intestinal epithelial cells (IECs), as well as the immune mechanisms employed by distinct IEC subsets to promote homeostasis, emphasizing the central and active role that these cells play in host enteric defense.
Keywords: Animals; Antigens; Cell Communication; Dysbiosis; Epithelial Cells; Gastrointestinal Microbiome; Homeostasis; Host-Pathogen Interactions; Humans; Immune System; Immunity, Innate; Immunity, Mucosal; Intestinal Mucosa; Signal Transduction; intestinal epithelial cells; microbiota; mucosal immunity